PERANCANGAN MEDIA PROMOSI WISATA RELIGI ISLAM GRESIK SEBAGAI UPAYA MENGANGKAT POTENSI WISATA - Wardah, Lia; Bahruddin, Muh.; Riqoh, Abdullah Khoir (Jurnal ArtNouveau, 2013)
Gresik as an industrial city, has a wide array of potential in tourism including cultural tourism, religious tourism, and nature. But, not all potentials tourism maximized management and promotionÂ by the government of Gresik, especially religious tourism. So, there are not many people knows the potential of religious tourism of Gresik. The goal of design to find out how to Designing Media Campaign of religious tourism in Gresik as effort raised tourism potential. The design is done with a qualitative approach, namely observation, interviews, documentation and literature in order to formulate a design concept. The data were analyzed by reduction, categorization, sintesisasi, and conclusion (Moleong, 2006:288). From the analysis, it was found that the uniqueness by Islamic religious tourism in Gresik has not fully lifted to a wide audience. Lack of promotional efforts to be one of the obstacles that make the tourist potential has not been known. After going through the process of data analysis, found the keyword or concept design âPioneerâ its mean the person who started that first, people who paved the way, and leader. In this case âPioneerâ described that Islamic religious tourism in Gresik regency is leaders and the first spread of Islam in Java. In the design of media campaigns created specifically to raise the potential of Islamic religious tourism in Gresik regency, accentuate the power of the concept âPioneerâ and another uniqueness owned. The design refers to he principles of design. The result are expected to raise some of the Islamic religious tourism potential in Gresik regency.